Inverted‐V and low‐energy broadband electron acceleration features of multiple auroras within a large‐scale surge. Issue 9 (10th September 2013) - Li, Bin; Marklund, Göran; Karlsson, Tomas; Sadeghi, Soheil; Lindqvist, Per‐Arne; Vaivads, Andris; Fazakerley, Andrew; Zhang, Yongliang; Lucek, Elizabeth; Sergienko, Tima; Nilsson, Hans; Masson, Arnaud
Abstract: [1] Results are presented from a Cluster C2 satellite crossing through the acceleration region of multiple auroral structures within a large‐scale surge, simultaneously monitored by DMSP F17 imager data. The magnetic and electric field data are consistent with the auroral distribution at large and medium scales. We identify the quasi‐static acceleration above and below C2 orbit by downgoing inverted‐V electrons and parallel electric potential drops, respectively. In the poleward surge region, within or adjacent to the inverted‐V arcs, intense low‐energy (broadband) electron fluxes are seen as well as a rough equality between ΔE/ΔB and the Alfvén velocity, suggesting that these are of Alfvénic origin. The most poleward and equatorward auroral structure is found to be Alfvénic and quasi‐static, respectively. In between, the structures are of mixed origin. We estimate the relative role of the acceleration processes by the contributions to the downward electron energy flux by electrons above and below 1.62 keV. Although these are local estimates, they should be representative also below Cluster altitude, except for two regions of intense downward Poynting flux, the power of which will be dissipated at lower altitudes and increasing the Alfvénic contribution. This is also supported by intense fluxes of low‐energy, broadband, upgoing electrons observed within these regions. Otherwise, the inverted‐V contribution dominates for most of the auroral structures observed by Cluster. The Alfvénic contribution to the mixed arc emissions is to extend these to higher altitudes, as shown by numerical simulation results. Key Points: Multiple aurora within a large‐scale surge Low‐energy broadband electron acceleration Inverted‐V electron acceleration